Management of Congenital Diaphragmatic Hernia Treated With Extracorporeal Life Support: Interim Guidelines Consensus Statement From the Extracorporeal Life Support Organization. Issue 2 (February 2021) - Guner, Yigit; Jancelewicz, Tim; Di Nardo, Matteo; Yu, Peter; Brindle, Mary; Vogel, Adam M.; Gowda, Sharada H.; Grover, Theresa R.; Johnston, Lindsay; Mahmood, Burhan; Gray, Brian; Chapman, Rachel; et al.
Abstract : The management of infants with congenital diaphragmatic hernia (CDH) receiving extracorporeal life support (ECLS) is complex. Significant variability in both practice and prevalence of ECLS use exists among centers, given the lack of evidence to guide management decisions. The purpose of this report is to review existing evidence and develop management recommendations for CDH patients treated with ECLS. This article was developed by the Extracorporeal Life Support Organization CDH interest group in cooperation with members of the CDH Study Group and the Children's Hospitals Neonatal Consortium.